2020
DOI: 10.1093/glycob/cwaa080
|View full text |Cite
|
Sign up to set email alerts
|

Topsy-turvy binding of negatively charged homogalacturonan oligosaccharides to galectin-3

Abstract: Galectin-3 is crucial to many physiological and pathological processes. The generally accepted dogma is that galectins function extracellularly by binding specifically to β(1➔4)-galactoside epitopes on cell surface glycoconjugates. Here, we used crystallography and NMR spectroscopy to demonstrate that negatively charged homogalacturonans (HG, linear polysaccharides of α(1➔4)-linked-D-galacturonate (GalA)) bind to the galectin-3 carbohydrate recognition domain. The HG carboxylates at the C6 positions in GalA ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Since the first observation of Nangia-Makker et al [56]-that modified citrus pectin can bind to Gal-3 and act as its competitive inhibitor, many studies have reported the direct interaction between these molecules. Binding between various types of pectins or polysaccharides with Gal-3 has been detected via nuclear magnetic resonance [57,58], surface plasmon resonance [59,60], and atomic force microscopy [61], as well as fluorescence microscopy and flow cytometry [60]. The inhibition of the Gal-3-mediated hemagglutination of erythrocytes by pectins has also been observed [29,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first observation of Nangia-Makker et al [56]-that modified citrus pectin can bind to Gal-3 and act as its competitive inhibitor, many studies have reported the direct interaction between these molecules. Binding between various types of pectins or polysaccharides with Gal-3 has been detected via nuclear magnetic resonance [57,58], surface plasmon resonance [59,60], and atomic force microscopy [61], as well as fluorescence microscopy and flow cytometry [60]. The inhibition of the Gal-3-mediated hemagglutination of erythrocytes by pectins has also been observed [29,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides may also interact with the N-terminal tail (NT) of Gal-3, a process that is likely modulated by NT proline isomerization [ 109 ], and macromolecular assemblies of complex polysaccharides can interact with Gal-3 with synergestic effects on function [ 110 ]. In addition, Zheng et al [ 111 ] showed that negatively-charged homogalacturonan-derived oligosaccharides bind to the Gal-3 CRD canonical site in a “topsy-turvy” fashion with their reducing end residue (as opposed to the non-reducing end residues as in lactose) interacting with the conserved tryptophan. This scenario may well be how galectins bind to heparan sulfate-based glycoconjugates on the surfaces of cells, as further exemplified by the binding of keratan sulfate and related saccharides to Gal-1, -3, -7 and -9N [ 112 ].…”
Section: Galectinsmentioning
confidence: 99%
“…Polysaccharides may also interact with the N-terminal tail (NT) of Gal-3, a process that is likely modulated by NT proline isomerization [109], and macromolecular assemblies of complex polysaccharides can interact with Gal-3 with synergestic effects on function [110]. In addition, Zheng et al [111] showed that negativelycharged homogalacturonan-derived oligosaccharides bind to the Gal-3 CRD canonical site in a "topsy-turvy" fashion with their reducing end residue (as opposed to the non-reducing end residues as in lactose) interacting with the conserved tryptophan. This scenario may well be how galectins bind to heparan sulfate-based glycoconjugates on the surfaces of cells, as further exemplified by the binding of keratan sulfate and related saccharides to Gal-1, -3, -7 and -9N [112].…”
Section: Galectinsmentioning
confidence: 99%